The Origins of Common Identity: Evidence from Alsace-Lorraine - Sirus Dehdari; Kai Gehring (Center for Economic Studies and ifo Institute (CESifo), 2019)
The quasi-exogenous division of the French regions Alsace and Lorraine after the Franco-Prussian War allows us to provide evidence about group identity formation within historically homogeneous regions. We use several measures of stated and revealed preferences at the municipal-level in a geographical regression discontinuity design. More nation-state repression is associated with a strengthening of regional identity in the short, medium, and long run. We explain this in a model and document that the establishment of regionalist organizations is a key mechanism to strengthen identity. A relatively stronger regional compared to national identity is associated with preferences for more regional decision-making.
Keywords: D91; H70; N40; Z19; 330; group identity; nation-building; repression; assimilation; regional identity; border regions; Alsace-Lorraine